Dental Hygienists' Cognitive Process in Periodontal Soft Tissue Charting - (:unkn) unknown (My University, 2015)
Introduction: Dental hygienists have not had the opportunity to be involved in the design and development of the periodontal soft tissue charts and the surrounding interface features that are used while examining dental patients in daily practice. In some cases, dentists are able to give their opinions, wants, and needs into the development of the health information systems that they use on a daily basis, but too often, the dental hygienist is forgotten about and no input is ever given to the developers from the dental hygienists. This project considers the impact of well-designed interfaces on effectiveness and workflow particularly in regard to the dental hygienists. It is focused on improving the surrounding interface of the electronic periodontal soft tissue chart in order to provide effective and efficient patient-centered cognitive support to the dental hygienist during a patient's periodontal examination. Current periodontal soft tissue charts used in daily practice lack dental hygienists’ input during development. This study will fill a gap in knowledge by defining dental hygienists’ workflow and needs, and then proposing a layout and prototype for a periodontal soft tissue chart interface that will meet those needs. Methodology: Using a multi-phase methodology (ethnographic observations, focus groups, and cognitive task analysis) the wants and needs of practicing dental hygienists were defined. Based on the results of the ethnographic observations, focus groups, and cognitive task analysis sessions, a prototypical periodontal soft tissue chart interface was developed. The prototype then underwent usability testing by dental hygienists to compare its usability versus the existing commercial software, Dentrix. Results: Ten dental hygienists participated in the ethnographic observations, focus groups, and cognitive task analysis sessions. The wants and needs of dental hygienists were determined, as well as a “common” workflow among them. Using these results, the prototypical periodontal soft tissue chart interface was developed. Usability testing comparing Dentrix and the prototype revealed that the dental hygienists completed tasks on the prototype with greater success and speed than on Dentrix. Furthermore, the dental hygienists provided more positive comments toward the prototype than Dentrix. Conclusions: This study exhibits the need to properly involve the end users – dental hygienists – in the creation of a prototypical periodontal soft tissue chart interface. Health information systems need to involve the end users at all stages in the development process in order to design and develop a system that is efficient and usable for them.
Keywords: Dental Hygienist; Dental Informatics; Human-Computer Interaction; Usability Testing